Addressing Uncertainties in Complex Manufacturing Environments: A Multidisciplinary Approach - Dhiman, Hitesh; Plewe, D. A.; Röcker, Carsten (Advances in Manufacturing, Production Management and Process Control)
With the introduction of intelligent and autonomous systems into factory environments, workplaces where human employees work alongside digital counterparts will become increasingly informational. We develop a generic framework for hypothetical workplaces to investigate how complexities create to uncertainties. Complexity may be explained through the Level of Abstractions used to model a system, and it is encountered in its dynamic form as an alteration of information flow between agents in a phenomenological relationship. Analyzing these systems as ‘information flows’ brings to light the uncertainity(ies) the workers of the future will have to cope with. We develop first concepts that can be used to develop heuristics to manage these uncertainties in complex manufacturing environments. These heuristics may also be useful in creating optimized workplaces that combine the individual abilities of both humans and machines. The framework proposed in this paper may be subject for an empirical validation of these heuristics in the future.
Keywords: Uncertainties; Complexity; Human-machine interaction